Safety and Feasibility of Transcranial Direct Current Stimulation for Cognitive Rehabilitation in Patients With Mild or Major Neurocognitive Disorders: A Randomized Sham-Controlled Pilot Study - Inagawa, Takuma; Yokoi, Yuma; Narita, Zui; Maruo, Kazushi; Okazaki, Mitsutoshi; Nakagome, Kazuyuki (Frontiers in Human Neuroscience, 2019)
Introduction: Transcranial direct current stimulation (tDCS) is a potentially novel strategy for cognitive enhancement in patients with mild or major neurocognitive disorders. This study aims to assess the safety and efficacy of tDCS during cognitive training on cognitive functioning in patients with mild or major neurocognitive disorders. Methods: This study was primarily a single arm for safety, and secondary a two-arm, parallel, randomized, sham-controlled trial for potential efficacy. Patients with mild or major neurocognitive disorders were recruited. The participants and raters were blinded to the group assignment. The participants in the active arm received tDCS (anodal; F3, cathodal, Fp2, 2A, 20 min) twice daily for five consecutive days, whereas those in the sham arm received the same amount of sham-tDCS. Calculation and reading tasks were conducted in both arms as a form of cognitive intervention for 20 min during tDCS. The primary outcome was the attrition rate during the trial in the active arm, which is expected to be less than 10%. The secondary outcomes were the between-group differences of adjusted means for several cognitive scales from baseline to post-intervention and follow-up. Results: Twenty patients (9 women [45%]), with a mean (standard deviation) age of 76.1 years participated; nine patients (45%) with minor neurocognitive disorders and 11 (55%) with major neurocognitive disorders were randomized, and 19 of them completed the trial. The attrition rate in the active arm was 0%, with no serious adverse events. Further, in the Intention-to-Treat analysis, patients in the active arm showed no statistically significant improvement compared with those who received sham in the mean change scores of the Mini-Mental State examination (0.41; 95% CI [-1.85; 2.67] at day five, 1.08; 95% CI [-1.31; 3.46] at follow-up) and Alzheimer’s Disease Assessment Scale—Cognition Subscale (1.61; 95% CI [-4.2; 0.98] at day five, 0.36; 95%CI [-3.19; 2.47] at follow-up). Conclusions: These findings suggest that tDCS is safe and tolerable, but causes no statistically significant cognitive effects in patients with mild or major neurocognitive disorders. Additional large-scale, well-designed clinical trials are warranted to evaluate the cognitive effects of tDCS as an augmentation to cognitive training.